Comparison of ablation performance between dual internally cooled wet tip and conventional dual internally cooled tip radiofrequency electrodes: an experimental study in ex vivo bovine liver. (1st January 2021) - Cha, Dong Ik; Lee, Min Woo; Jeong, Woo Kyoung; Ha, Sang Yun; Ahn, Soo Hyun; Rhim, Hyunchul; Lim, Hyo Keun
Abstract: Objective: To evaluate the performance of dual internally cooled wet tip (ICWT) radiofrequency electrodes in comparison to dual internally cooled tip (ICT) electrodes. Methods: Twenty ablation zones were created for each type of electrodes. Planned procedure time was 6 min. Diameters of the ablation zone along the x-, y-, and z-axes (Dx, Dy, and Dz), ablation zone sphericity, quantitative sphericity measurement, and ablation volume were measured and compared between the two electrode types. Circularity of the ablation zone on the surface with x- and z- axes (zx plane) and amount of energy applied were also compared. Results: Dx and Dz were significantly longer with ICWT than those with ICT (Dx: 3.0 vs. 2.8 cm, p = .018; and Dz: 2.7 vs. 2.3 cm, p < .001, respectively). Dy was not significantly different (3.0 vs. 2.9 cm, p = .220). Moreover, 85% (17/20) and 30% (6/20) of ablation zones from ICWT and ICT were spherical ( p = .001), respectively. Quantitative measurement showed that ICWT was more spherical compared to ICT (0.962 vs. 0.881, p = .001). The ablation volume was also significantly higher with ICWT (11.55 vs. 9.45 cm3, p = .003). The ablation zone on the zx plane was more circular with ICWT (0.907 vs. 0.883, p = .028). The amount of energy applied was significantly bigger with ICWT (18508 vs. 16998 WS, p = .003). Conclusion: Dual ICWT electrodes were better able to create more spherical and larger ablation zones than dual ICT electrodes.